Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. Educational principles derived from the dialogue of the Prophet, may God bless him and grant him peace, with his wives and their applications in the Muslim family Dr. Noura Hammoud Al-Mutairi 2. The relationship between Alexithymia and peer attachment among female students of Hail University Ms. Bashayr Nawaf Al-Shammari 3. Sports activities and their relationship to mental health and academic achievement among children with autism spectrum disorder from the point of view of specialists Dr. Mersal Abdullah Suleiman Mersal 4. The Level of Bullying among Students with Learning Disabilities from the Point of View of their Parents in the City of Makkah Ms. Saliha Hussein Mohammed Alharthi, Co-Prof. Nawal Ahmad Elbadawy Abu Alula 5. The effectiveness of cognitive-behavioral therapy for obsessive-compulsive disorder by using remote digital knowledge media in a sample in my extended family (Al-Jazeera State- Sudan) Co-Prof. Bakhita Mohammed zain Ali 6. Proposed Quality Standards in the RTI Implementation at the LD programs: Faculty perspectives Ms. Hanan Hussain Al Dukain, Dr. Alwiah Abdullah Alsaggaf 7. Family educational care of the blind children and its relationship to their social adaptation Dr.Abdelrahman Gibreel Imam 8. Artificial Intelligence in Education: A Future Vision Dr. Zohor Mohammed Al-Areeshi